x2 + 3x - 18 = 0 (x - 3)(x + 6) = 0 x = 3 or -6
1 and 2
The factors are (x + 6) and (x - 3)
x2 + 3x - 40 = (x + 8)(x - 5)
If you factor x2 - 3x - 10, you'll get (x-5) (x+2). If your equation is x2 - 3x -10 = 0, then x = 5, and x = -2.
x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0
3x-1 = 11 3x = 11+1 3x = 12 x = 4 Therefore: x2+2 = 18
X2 + 3X - 18 = 0What two factors of - 18 add up to 3 ??(X - 3)(X + 6)============so, by the zero sum rule,X = 3X = - 6
x2 plus 3x plus 3 is equals to 0 can be solved by getting the roots.
x2 + 3x - 18 = 0 (x - 3)(x + 6) = 0 x = 3 or -6
-2
xx+3x+7=6x+18 xx+3x+7-(6x+18)=6x+18-(6x+18) xx-3x-11=0 Factors of -11: 1,-11 -1,11 Doesn't factor evenly, use quadratic
3x-1 = 11 3x = 11+1 = 12 x = 12/3 = 4 Therefore: x2 + 2 = 16 + 2 = 18
x2 + 3x + 7 = 5 ∴ x2 + 3x + 2 = 0 ∴ (x + 1)(x + 2) = 0 ∴ x ∈ {-2, -1}
x = 2
x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0
x2 + 3x - 18 = x2 + 6x - 3x - 18 = x(x + 6) - 3(x + 6) = (x + 6)(x - 3)